Campus Mosque Management As A Character Education Laboratory - Puput Mulyono; Singgih Purnomo (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Today, character education is an urgent need for the Indonesian nation due to the moral degradation that has infected the community even among students. The campus mosque is a place to foster strategic quality people in the formation of student character. The purpose of this study was to determine the management and role of campus mosques in shaping student character at Duta Bangsa University Surakarta. This research uses descriptive qualitative research with data collection techniques data collection techniques using observation, interviews and documentation. The results of this study are First, forming a mosque board. Second, formulating the vision, mission, values and goals of the mosque as a character education laboratory. Third, compiling a mosque activity program as a character education laboratory. Fourth, implementing the mosque activity program as a character education laboratory. Fifth, assessing the success of the mosque activity program as a character education laboratory. Campus mosques at Duta Bangsa University Surakarta, which are currently spread across three locations and have various programs and activities that have been recognized for their benefits, can take on the role of a character education laboratory.